A generic architecture to design Cyber-Physical and Human Systems. Issue 5 (2020) - Berger, Thierry; Sallez, Yves; Dequidt, Antoine; Trentesaux, Damien
Abstract: Although Cyber Physical Systems are widely implemented in many areas, model architecture for Human and CPS remains insufficiently studied. In this paper, a generic model is proposed to describe the architecture of a Cyber-Physical & Human System. This model deals respectively with the cognitive levels of the decisional process, the nature of the informative details and the sharing of the tasks execution between Humans and machines. Finally, the model is applied to a case study in the healthcare domain.